The association between lactate dehydrogenase to serum albumin ratio and in-hospital mortality in patients with pulmonary embolism: a retrospective analysis of the MIMIC-IV database - Hu, Jingjing; Zhou, Yidan (Frontiers in Cardiovascular Medicine, 2024)
Background: Lactate dehydrogenase (LDH) and albumin (ALB) ratio were found to be significantly correlated with mortality in pulmonary embolism (PE). However, data regarding LDH/ALB ratio (LAR) in acute pulmonary embolism (acute PE) patients are scanty. Therefore, this study aims to investigate the association between LAR and the risk of mortality in acute PE patients. Methods: A retrospective cohort study was conducted on patients with acute PE represented in the Medical Information Mart for Intensive Care IV (MIMIC-IV). The receiver operating characteristic (ROC) curve analysis and calibration curve were used to assess the accuracy of the LAR for predicting mortality in patients with acute PE. We utilized Cox regression analysis to determine adjusted hazard ratios (HR) and 95% confidence intervals (CI). Survival curves was used to evaluate a connection between the LAR and prognosis in patients with acute PE. Results: The study comprised 581 patients, and the 30-day all-cause mortality rate was 7.7%. We observed a higher LAR in the death group compared to the surviving group (21.24±21.22 vs. 8.99±7.86, P<0.0001). The Kaplan-Meier analysis showed that patients with an elevated LAR had a significantly lower likelihood of surviving the 30-day mortality compared to those with a low LAR. Cox regression analysis showed that LAR (HR = 1.04, 95% CI: 1.03-1.05) might have associations with 30-day mortality in acute PE patients. This result was supported by sensitivity analyses. According to the results of the ROC curve analysis, the LAR's prediction of 30-day mortality in patients with acute PE yielded an area under the ROC curve of 0.73. Calibration curve showed LAR is well calibrated. Conclusion: Our research suggests LAR monitoring may be promising as a prognostic marker among acute PE patients.